DETERMINAN INDEKS HARGA SAHAM GLOBAL PERIODE 2019-2022 MENGGUNAKAN PENDEKATAN ERROR CORRECTION MODEL (ECM) - Anggraeni Dwi Ningrum; Lestari Sukarniati; Firsty Ramadhona Amalia Lubis; Nenis Tri Atikah (Program Studi Ekonomi Pembangunan, 2026)
This study aims to analyze the influence of global stock price indices on the Jakarta Composite Index (JCI) on the Indonesia Stock Exchange for the 2019–2022 period. The method used is a quantitative approach with the Error Correction Model (ECM) to identify short-term and long-term relationships between variables. The data used is monthly time series data covering the Dow Jones Industrial Average (DJIA), FTSE 100, Hang Seng Index (HSI), Kuala Lumpur Composite Index (KLCI), Nikkei 225, and Straits Times Index (STI). The results show that in the short term, the KLCI, Nikkei 225, and STI have a significant positive effect on the JCI, while the DJIA, FTSE 100, and HSI have no effect. In the long term, the DJIA and HSI have a significant negative effect on the JCI, while the KLCI, Nikkei 225, and STI have a significant positive effect, and the FTSE 100 remains unaffected. A significant error correction term coefficient indicates the existence of an adjustment mechanism towards long-term equilibrium. In conclusion, there is integration of the Indonesian capital market with several global markets, especially in the Asian region, which influences the movement of the JCI.